The Difference in Perceived Risk by Gender Among Novice Investors: before and during Covid-19 Pandemic - Eko Ganiarto; Farida Komalasari (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2022)
Understanding of risk is very important for investors, especially for novice investors.  Their perception about risk, whether for male or female novice investor is interesting to study. Likewise, in the current Covid-19 pandemic situation, analyzing the differences in the perceived risk between the two is interesting also to do, since it determines their investment behavior. At the end, their investment behavior will affect the economic condition. This quantitative study aims to know whether there are any differences in perception of investment risk between male and female novice investors, both before and during the Covid-19 pandemic. Beside that, this study also examines the interaction between gender and other demographic factors (age, education, occupation and income) to differentiate perceived risk, both before and during Covid-19 pandemic. The perceived risk variable used in this study was measured using five statement indicators. Data were obtained from 299 novice investor respondents in the Indonesian Stock Exchange in 2020, then processed and analyzed using the paired t-test for the mean difference method. The results showed that there were differences in perceived risk between male and female investors in the period before the Covid-19 pandemic. Meanwhile, during the Covid-19 pandemic, there was no difference between the two. Beside that there was a difference in perceived risk of male/female between before and during the Covid-19 pandemic. Meanwhile, age and occupation were the factors that differentiate perceived risk, especially before Covid-19 pandemics, while education, and income are not.